Social networks: a contribution to the teaching of critical reading - Pinto Maldonado, Luz Katherine (2021)
This article shows how social networks have become part of the life of any person and even more so in university students who have been born in the digital age. Under this context, the reading field has seen the need to evolve and adapt to the world in which it faces, which is why the booktubers and bookstagrammers were born, who today are the favorite analysts of young readers. It is necessary to bear in mind that the types of texts that these content creators promote are limited, since most of them only focus on offering reviews of children’s or young people’s Literature,  very few are open to the development of critical reading, this merits a problem because it pigeonholes students to the conventional. Therefore, it is considered important to change this reality, using this information technology that is already successful in social networks, but this time with the intervention of the teaching professional who from his position will contribute with novel strategies to guide the development of this production of educational resources in order to improve the quality of information and the treatment of critical reading.